(3GdeHOC hGdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEfi CQjO Cf COd ai gPg GdebGdI Ydi MbjbI eG YfO GdeTGFjf GdeMUdjf ef MGd GdeHOC hGdeYGO JbQjHkG s
(3BNQgG (B:s
(3hEf cGfJ ef GdbhI HMSH GdChdi Cf JPcQ hdcf jDKQ GdEjVGM hGdGNJUGQ ajeG fQi hfaYd Je GdcJGH hddg GdMeO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(1584/1) s
Keywords: (3GdadSaI hGdefWbs